On the fertilizer particle motion along the vane of centrifugal spreader disc assuming pure sliding of the particle - Cerović, Vera B; Petrović, Dragan V; Radojević, Rade L.; Barać, Saša R.; Vuković, Aleksandar (Journal of Agricultural Sciences (Belgrade), 2018)
At present, spreading of mineral fertilizers in Europe is most commonly performed using centrifugal disk spreaders with attached vanes. The motion of ideal spherical homogeneous fertilizer particle along the straight vane attached to flat rotating disc is analyzed in this paper. The analysis is performed in the non-inertial reference coordinate system. From the assumptions introduced to enable analytical describing of the real particle motion, as well as the general tools of solid mechanics, the ordinary in-homogenous second-order differential equation having constant coefficients arises. Its solution represents an approximation of the relative motion of fertilizer particle along the straight radial vane fixed to flat horizontal disc rotating at constant angular velocity. However, solution of this kind can be very useful for optimization of centrifugal spreader working parameters.